Potential ecological footprints of active pharmaceutical ingredients: an examination of risk factors in low-, middle- and high-income countries - Kookana, Rai S. (The Royal Society, 2014)
Active pharmaceutical ingredients (APIs) can enter the natural environment during manufacture, use and/or disposal, and consequently public concern about their potential adverse impacts in the environment is growing. Despite the bulk of the human population living in Asia and Africa (mostly in low- or middle-income countries), limited work relating to research, development and regulations on APIs in the environment have so far been conducted in these regions. Also, the API manufacturing sector is gradually shifting to countries with lower production costs. This paper focuses mainly on APIs for human consumption and highlights key differences between the low-, middle- and high-income countries, covering factors such as population and demographics, manufacture, prescriptions, treatment, disposal and reuse of waste and wastewater. The striking differences in populations (both human and animal), urbanization, sewer connectivity and other factors have revealed that the environmental compartments receiving the bulk of API residues differ markedly between low- and high-income countries. High sewer connectivity in developed countries allows capture and treatment of the waste stream (point-source). However, in many low- or middle-income countries, sewerage connectivity is generally low and in some areas waste is collected predominantly in septic systems. Consequently, the diffuse-source impact, such as on groundwater from leaking septic systems or on land due to disposal of raw sewage or septage, may be of greater concern. A screening level assessment of potential burdens of APIs in urban and rural environments of countries representing low- and middle-income as well as high-income has been made. Implications for ecological risks of APIs used by humans in lower income countries are discussed.